Donor site morbidity of calcaneal, distal tibial, and proximal tibial cancellous bone autografts in foot and ankle surgery. A systematic review and meta-analysis of 2296 bone grafts. Issue 6 (August 2022) - Attia, Ahmed Khalil; Mahmoud, Karim; ElSweify, Kareem; Bariteau, Jason; Labib, Sameh A.
Graphical abstract: Abstract: Purpose: This study aims to report on the safety and donor site morbidity of the distal lower extremity (calcaneal, proximal, and distal tibial) cancellous bone autografts. We summarized the findings in a comprehensive infographic illustration. We are unaware of any similar meta-analyses to date. Methods: Following the PRISMA guidelines, two independent investigators searched MEDLINE (PubMed), EMBASE, SCOPUS, Google Scholar, and Cochrane databases in December 2020 using the following keywords and their synonyms: ("bone graft", "donor site morbidity", "calcaneal graft", "proximal tibia graft", and "distal tibia graft"). Besides, the reference lists from previous review articles were searched manually for eligible studies. The primary outcomes of interest were (1) chronic pain, (2) fracture, and (3) infection, whereas the secondary outcomes were (1) neurological complications, (2) sensory disturbance and hypertrophic scars, (3) other complications such as shoe-wear difficulties and gait disturbance. Inclusion criteria were: studies on complications and adverse events of lower extremity bone autografts (calcaneal, proximal tibial, and distal tibial bone autografts) reporting at least one of the desired outcomes. Studies not reporting any of the outcomes of interest or if the full text is not available in English were excluded. Studies reporting on bone marrow aspirate or autografts for non-orthopedic indications were also excluded. Results: After the removal of duplicates, a total of 5981 studies were identified. After screening those records, 85 studies remained for full-text assessment. Out of those, 15 studies qualified for the meta-analysis with a total of 2296 bone grafts. Out of those grafts, 1557(67.8%) were calcaneal grafts, 625 (27.2%) were proximal tibial grafts, and 114 (5%) were distal tibial grafts. In calcaneal bone grafts, there were 28 cases of chronic pain [1.97%, CI:1.10−2.50%, I 2  = 66%], 5 fractures [0.32%, CI: 0.10−0.60%, I 2  = 0%], 20 sural neuritis [1.28%, CI:0.70−1.80%, I 2  = 0%), and no wound infections. In proximal tibial grafts there were 13 cases of chronic pain [2.08%, CI: 1.01−3.2%, I 2  = 34.5%], 1 fracture [0.16%, CI:0.10−0.50%, I 2  = 0%], and 3 superficial wound infections [0.48%, CI: 0.10−1.01, I 2  = 0%]. In the distal tibial grafts there were no cases of chronic pain or wound infections, 1 fracture [0.90%, CI: 0.80−2.6%, I 2  = 0%], and 5 saphenous neuritis [4.5%, CI: 0.70−8.40%, I 2  = 65%]. Conclusion: Calcaneal, distal tibial, and proximal tibial bone autografts are safe with a low rate of overall and major complications. We report an overall complication rate of 6.8%, which is less than half of that previously reported for iliac crest grafts. The authors recommend using distal lower extremity grafts for foot and ankle primary surgeries instead of iliac crest grafts when indicated. Clinical trials with a large sample size are required.